Stress Response Profiles and Physical Aggression in Early Childhood - Meijer, Elja E. J.; Huijbregts, Stephan C. J.; Goozen, Stephanie H. M. Van; Swaab, Hanna (Advances in Social Sciences Research Journal, 2024)
This study examined the applicability of the four stress response patterns proposed by the Adaptive Calibration Model (ACM; Del Giudice et al., 2011) in 12-month-old children (N = 214; 116 boys) and their associations with physical aggression at 12, 20, and 30 months of age. Salivary alpha-amylase (sAA) and pre-ejection period (PEP) served as indices of the sympathetic nervous system, respiratory sinus arrhythmia as an index of the parasympathetic nervous system, salivary cortisol as an index of the hypothalamic-pituitary-adrenal axis, and heart rate as a measure of overall autonomic nervous system activity. A fear challenge was administered at 12 months to measure baseline, response, and recovery levels of the stress systems, while maternal reports were used to evaluate physical aggression at the various time points. Through latent profile analysis, three stress response profiles were identified: (1) ANS Responders, (2) Moderate Responders (across all stress systems), and (3) Hormonal Responders. Despite some deviations, each profile could be associated with a corresponding ACM stress response pattern, primarily due to the inclusion of both sAA and PEP as measures of sympathetic activity. At 12 months, ANS Responders showed higher levels of physical aggression, whereas Hormonal Responders exhibited higher levels of physical aggression at 20 months. The findings confirm that differences in stress response patterns can be observed as early as 12 months of age. Moreover, this study emphasizes the importance of using multiple indices of stress responsivity to identify such distinct patterns. Finally, stress response profiles that differ from the most common (moderate) profile, are associated (albeit not consistently) with higher levels of physical aggression at different ages during early childhood.